Water and wastewater treatment : a guide for the nonengineering professional - Drinan, Joanne (CRC Press, 2013)
"Designed to meet the information needs of professionals without an engineering background, this book describes and explains in simple, non-mathematical terms the unit processes used to treat both drinking water and wastewater. The text presents each unit process, states what function(s) it performs, illustrates what equipment it uses, and explains its role in the process of purifying or cleaning water. Now featuring summary sections, each chapter in this second edition has been fully updated and revised to present the latest regulatory and technological advancements as well as new drinking and wastewater regulatory requirements"--